1982
DOI: 10.1128/jcm.16.5.847-850.1982
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for cultivation and isolation of Chlamydia trachomatis

Abstract: McCoy cells treated with cycloheximide, iododeoxyuridine, and DEAE-dextran and untreated McCoy cells were inoculated with two stock strains of Chlamydia trachomatis and with 231 urethral specimens from men, 53 (23%) of which contained C. trachomatis. Isolation rates, number and quality of inclusions, and quality of the cell monolayers were compared. There were no significant differences between the isolation rates in the four systems, although the most isolations were made in the untreated and cycloheximide-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The combined DEAE-D and cycloheximide treatment resulted in an enhancement of the size of inclusions with little reduction in the number of inclusions. Several investigators have reported on the cycloheximide enhancement of the size of TRIC inclusions in McCoy cells (4,19,20). These investigators have also reported an increase in the number of inclusions detected by iodine staining in the cycloheximidetreated cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined DEAE-D and cycloheximide treatment resulted in an enhancement of the size of inclusions with little reduction in the number of inclusions. Several investigators have reported on the cycloheximide enhancement of the size of TRIC inclusions in McCoy cells (4,19,20). These investigators have also reported an increase in the number of inclusions detected by iodine staining in the cycloheximidetreated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cycloheximide treatment has been used extensively for the cultivation of TRIC organisms in McCoy cells (4,19,20). However, the effect of this antibiotic on the propagation of TRIC organisms in HeLa 229 has not been investigated.…”
Section: Fig 2 Effects Of Deae-mentioning
confidence: 99%
“…The diagnosis of a C. trachomatis infection, e.g., urethritis or cervicitis, is primarily dependent upon isolation by cell culture procedures. McCoy cells and HeLa 229 cells are commonly used, and various cell treatments have been described to enhance the sensitivity of the assay (1)(2)(3)(4)(5)(6)(7)(8)(9)11). Most authors used one cell type and one or more laboratory strains.…”
mentioning
confidence: 99%
“…However, these strains have had different histories of laboratory passage. The investigators studying the impact of modifications on the isolation rate in clinical specimens (1,2,5,6,9,11) always used one type of cell culture.…”
mentioning
confidence: 99%
“…The current accepted methods of isolation of C. trachomatis are generally modifications of the in vitro cell culture method first introduced by Gordon et al (4). The conventional procedure is laborious and cumbersome and requires a lengthy incubation period before and after infection of the McCoy cell monolayers, making it impractical for routine testing of large numbers of specimens (1).…”
mentioning
confidence: 99%